Interactions of fertilisation and crop productivity in soil nitrogen cycle microbiome and gas emissions - L. Kuusemets; Ü. Mander; J. Escuer-Gatius; A. Astover; K. Kauer; K. Soosaar; M. Espenberg (SOIL)
Fertilised soils are a significant source of nitrous oxide (N2O), a highly active greenhouse gas and a stratospheric ozone depleter. Nitrogen (N) fertilisers, while boosting crop yield, also lead to N2O emissions into the atmosphere, impacting global warming. We investigated relationships between mineral N fertilisation rates and additional manure amendment with different crop types through the analysis of abundances of N cycle functional genes, soil N2O and N2 emissions, nitrogen use efficiency (NUE), soil physicochemical analysis and biomass production. Our study indicates that N2O emissions are predominantly dependent on the mineral N fertilisation rate and enhance with an increased mineral N fertilisation rate. Crop type also has a significant impact on soil N2O emissions. Higher N2O emissions were attained with the application of manure in comparison to mineral fertilisation. Manure amendment also increased the number of N cycle genes that are significant in the variations of N2O. The study indicates that N2O emissions were mainly related to nitrification in the soil. Quantification of nitrogen cycle functional genes also showed the potential role of denitrification, comammox (complete ammonia oxidation) and dissimilatory nitrate reduction to ammonium (DNRA) processes as a source of N2O. Our study did not find soil moisture to be significantly linked to N2O emissions. The results of the study provide evidence that, for wheat, a fertilisation rate of 80 kg N ha−1 is closest to the optimal rate for balancing biomass yield and N2O emissions and achieving a high NUE. Sorghum showed good potential for cultivation in temperate climates, as it showed a similar biomass yield compared to the other crop types and fertilisation rates but maintained low N2O emissions and N losses in a mineral N fertilisation rate of 80 kg N ha−1.